PHILOSOPHY OF THANKSGIVING: https://doi.org/10.5281/zenodo.14763208 - Ismoilov , Sobirjon (Journal of Contemporary World Studies, 2025)
In this article, the content and interpretations of the concept of Thanksgiving are revealed based on the interpretations of verses and scribes.